Application of Rapid Multiplication Technique Using Mini Cutting and NPK Compound Fertilizer to Increase Production of Sweet Potato Cuttings (Ipomoea batatas L.) - Dewi, Ni Kadek Ema Sustia; Suhartanto, M. Rahmad; Suwarto, Suwarto (Journal of Tropical Crop Science, 2020)
Rapid Multiplication Technique (RMT) is a technique used to produce large scale cuttings of sweet potato in a short period by using mini cuttings and proper fertilizer management. The research was carried out from October 2019 to March 2020 and composed of two experiments The first experiment involved a randomized complete block design, with clones (“Ase Kapas” and “Ase Merah”) as the first factor, and tuber weight (150 ± 25 g, 250 ± 25 g, and 350 ± 25 g) as the second factor. The second experiment was arranged in a split-plot design involving different doses of NPK compound fertilizer (as main plot) and different source of cuttings (as subplots). The different doses included NPK 16:16:16 at 100 kg.ha-1 (0.3 g per polybag), 200 kg.ha-1 (0.6 g per polybag), 300 kg.ha-1 (0.9 g per polybag), and without fertilizer as control. The source of cuttings were from the tip, middle and bottom stem of the plants. Results showed that the “Ase Kapas” showed the highest number and the longest shoots, number of nodes, and length of vines. Additionally, tuber weight of ± 350 g produced the highest number of shoots. When it comes to NPK compound fertilizer treatment, a dose of 0.9 g per polybag increased cutting production in “Ase Kapas”, and also responded better to fertilizer treatment. On the other hand, dose of 0.3 g increased cutting production in “Ase Merah”. “Ase Kapas” produced more cuttings from the middle stem, whereas “Ase Merah” produced more cuttings from the . The application of RMT in “Ase Kapas” produced cuttings with ratio of 1:31, which is higher than those in “Ase Merah” with a ratio of 1:17.